Tea Fungus Beverages from Torch Ginger (Etlingera elatior): Total microbial, Physicochemical, and Antioxidant Activity - Fitrianto, Nur; Husen, Fajar; Samiyarsih, Siti; Ratnaningtyas, Nuniek Ina; Palindung, Lusia Seti; Azizah, Enur (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Functional beverages are needed to maintain health and fitness as a part of the instant lifestyle and degenerative diseases. The scientific findings on torch ginger (Etlingera elatior) flower (TGF) as a tea fungus beverage (Kombucha) are still limited. This research evaluated total microbes, physicochemical properties, and antioxidant activity 7 and 14 days after fermentation (daf) of TGF kombuchas. In addition, TGF in variant 0% (TGF0), 5% (TGF5), 10% (TGF10), and 15% (TGF15) are fermented with 3% of SCOBY, 20% culture, 1% green tea, and 10% sucrose. The antioxidant activities of TGF kombuchas were evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-Azino-bis 3-Ethylbenzothiazoline-6-Sulfonic Acid (ABTS) assay—the phenolic and flavonoid content using Folin-Ciocalteu method-gallic acid equivalent, and quercetin acid equivalent, respectively. The result showed that the fermentation time (p0.05) was affected by the properties of TGF kombuchas. Total microbes, physicochemical properties (pH, acidity, cellulose pellicle weight, phenolic, flavonoid content), and antioxidant activity were higher in 14 than in 7 days. Total soluble solid and total yeast count showed lower values in 14 days. The increase in total bacteria count, TGF15%, led to the highest increasing density from 8.08 ± 0.02Log CFU/mL on seven daf to 13.34 ± 0.04Log CFU/mL on 14 daf. The TGF 10% and 15% kombuchas in 14 dafs showed abundance in phenolic and flavonoid content, 121.45±1.07mg GAE/mL and 1.70±0.04 mg QAE/mL, respectively. During 14 daf and TGF 10%, the Kombucha of torch ginger flower demonstrated high antioxidant activity at 85.92±0.07% DDPH and 63.05±0.97ABTS. It is expected to aid future research into developing functional kombucha beverages.